Epidemiological, Morphometric, and Molecular Investigation of Cystic Echinococcosis in Camel and Cattle From Upper Egypt: Current Status and Zoonotic Implications - Gareh, Ahmed; Saleh, Amira A.; Moustafa, Samar M.; Tahoun, Amin; Baty, Roua S.; Khalifa, Refaat M. A.; Dyab, Ahmed K.; Yones, Doaa A.; Arafa, Mohsen I.; Abdelaziz, Amer R.; El-Gohary, Fatma A.; Elmahallawy, Ehab Kotb (Frontiers in Veterinary Science, 2021)
Cystic echinococcosis has been considered one of the major parasitic zoonoses which is associated with severe economic losses. The present study was undertaken to investigate the occurrence, organ distribution, cyst fertility and viability of cystic echinococcosis in slaughtered camels and cattle from various abattoirs in Assiut Governorate, Egypt. The work also involved morphological, morphometric, and molecular identification of the parasite. The occurrence of hydatid cysts was investigated in total number of 100 lungs of camels and 574 liver and lungs of cattle admitted to three slaughterhouses at Assiut Governorate, Egypt. Moreover, several individual variable factors, including organ involvement, age, sex, and hydatid cyst characteristics, were studied to identify their possible association with the occurrence of the disease. Genomic DNA was extracted from the hydatid cysts, followed by molecular identification of the parasite through amplification of ribosomal DNA internal transcribed spacer (ITS) regions. Hydatid cysts were found in 6 camels (6%) out of 100 inspected camels, while 5 hydatid cysts (0.87%) were detected in a total number of 574 cattle examined. The parasite was detected exclusively in lungs of camels, while lungs were the main organ infected by the parasite in cattle and one hydatid cyst was found in the liver (0.17%),. In camel, 66.7%, 16.65%, and 16.65%of detected cysts were fertile, sterile, and calcified, respectively, while in cattle, these percentages were 60%, 20%, and 20%, respectively. None of the studied variable factors were significantly associated with the occurrence of the disease in camels, with the exception that all cysts were found in the lung. Conversely, we found a significant association (P < 0.05) between the age and sex of the slaughtered cattle and the occurrence of hydatid cysts. In this respect, the rate of infection was higher in female cattle and those cattle more than 5 years (P < 0.05). The morphological, morphometric, and molecular studies confirmed the presence of the parasite. Taken together, our results concluded that camels and cattle play a potential role in maintaining the transmission cycle of this zoonotic parasite.